STUDIES IN MALESIAN PANDANACEAE VII. A REVIEW OF JAVANESE PANDANACEAE, WITH NOTES ON PLANTS CULTIVATED IN THE HORTUS BOGORIENSIS - Stone, Benjamin C. (Research Center for Biology, 1972)
In the light of recent monographic studies it has been found necessary to augment and revise to some extent the treatment of Javanese Pandanaceae in Backer & Bakhuizen van den Brinks